Effects of high-intensity interval training and resistance training on physiological parameters and performance of well-trained runners: A randomized controlled trial - Trevisol Possamai, Leonardo; Antonacci Guglielmo, Luiz Guilherme; Felix Salvador, Amadeo; Denadai, Benedito Sérgio [UNESP]; Do Nascimento Salvador, Paulo Cesar (Taylor & Francis, 2024)
This study aimed to verify the effects of 4 weeks of high-intensity interval training (HIIT), heavy (HRT) and explosive (ERT) resistance training on aerobic, anaerobic and neuromuscular parameters and performance of well-trained runners. Twenty-six male athletes were divided into HIIT (n = 10), HRT (n = 7) and ERT (n = 9) groups. Maximal oxygen uptake ((Formula presented.)) and the corresponding velocity ((Formula presented.)), anaerobic threshold (AT), running economy (RE), oxygen uptake kinetics, lower-body strength (1RM) and power (CMJ), and the 1500m and 5000m time-trial (TT) were determined. Improvements were observed in (Formula presented.) (mean difference (Δ): 2.6%; effect size (ES): 0.63) with HIIT, while AT was incresead in ERT (Δ: 4.3%; ES: 0.73) and HRT (Δ: 6.9%; ES: 0.72) groups. The CMJ performance was increased in ERT (Δ: 13.8%; ES: 1.03), HRT (Δ: 6.9%; ES: 0.55) and HIIT (Δ: 5.4%; ES: 0.34), whereas 1RM increase in HRT (Δ: 38.1%; ES: 1.21) and ERT (Δ: 49.2%; ES: 0.96) groups. HIIT improved the 1500m (Δ: −2.3%; ES: −0.62) and both HRT (Δ: −1.6%; ES: −0.32) and ERT (Δ: −1.7%; ES: −0.31) the 5000m TT. Despite performance adaptations were dependent on the training characteristics, both RT and HIIT model constitute an alternative for training periodization.
Keywords: Aerobic exercise; explosive exercise; oxygen uptake kinetics; resistance exercise; sport performance